Spatial Patterns, Opportunities and Determinants of MSMEs Employment in Township - Prakoso, Jalu Aji; Giovanni, Axel; Panjawa, Jihad Lukis (Universitas Negeri Semarang, 2021)
Research is divided into three sections that contribute to analyse the optimization of employment on large productive population in Magelang, First, to identify the spatial pattern and concentration based on MSME’s sector by considering comparative benefits. Secondly, to analyse the opportunity in its association with employments in MSMEs. Thirdly, the determinants of employment in MSMEs based on the field of industry, trading and service. This research employs quantitative approach by using Location Quotient and Economic Base Model as analysis for local and regional economic, as well as multiple linier regression analysis. The research indicates that each area demonstrates distinctive spatial pattern and concentration, in terms of industrial sector, trading and service. The opportunity for employment could be notified from basic employment and basic multiplier that exist in each area. There are certain areas that have high potential in new employments once the jobs are available in the sector of industry, trading and service. The determinants of employment of above three sectors have distinctive behaviour in responding the addition of new MSMEs and the addition of revenue. Hence, the appropriate stimulus could be formulated to optimize absorption of productive labour population based on the findings.